“Social Dumping” and “Letterbox Companies” – Interdependent or Mutually Exclusive Concepts in European Union Law? (Polish Yearbook of International Law, 2016)
This article investigates two interesting phenomena which exist within the framework of the European Union (EU) integration process, i.e. “social dumping” and “letterbox companies”. Taking into account recent EU legislative changes and commentaries in the available legal literature, it contends that the EU’s institutions and its Member States are aware of some negative effects that these phenomena may have for attaining one of the EU’s basic aims, that of a “highly competitive social market economy”, as provided in Article 3(3) (ex 2, as amended) of the Treaty on the European Union. The EU should be understood as being not only focused on the implementation of the Internal Market freedoms, but also the protection of social rights. “Social dumping”, and to a certain extent also “letterbox companies”, reduce the level of this protection. Posting of workers is a good example of an EU integration area where “social dumping” and “letterbox companies” occur on a quite large scale and create some real practical problems. If we can clearly understand the concepts underlying these phenomena and their possible relationships, it would be easier to find a solution to reduce their negative effect on the protection of social rights. This article researches these issues and presents possible solutions to problems they give rise to.